The Role of School’s Principal and Peer Observation in Improving the Professional Quality of Teachers - Erikawati, Erikawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This research aims to investigate the role of observation by school principals and colleagues in improving the professional quality of teachers in the education environment.This research examines the role of principal and peer observations in improving the professional quality of teachers using the review article writing method.Research conducted by researchers at SD N 163 Palembang shows that observations by the principal and colleagues contribute to improving the professional quality of teachers. Observation is the same as supervision, only the name has changed in the Independent Curriculum. Observations or direct observations from other people to provide feedback can be carried out by the Principal and colleagues so that the professional quality of teachers can be improved. The principal acts as a leader and director in the teacher evaluation and self-development process, while colleagues provide social support and constructive feedback. This research makes a new contribution by exploring the role of observation by school principals and colleagues in an integrated manner in the context of increasing teacher professionalism. This approach highlights the importance of collaboration and support between school members in teacher professional development. Important implications for educational management practice, emphasizing the need to develop observation systems that are oriented towards continuous learning and holistically increasing teacher professionalism.